Preoperative Radiological Assessment of The Total Knee Arthroplasty - Atilla Hikmet Cilengir; Suat Dursun; Kazim Ayberk Sinci; Ozgur Tosun (Forbes Tıp Dergisi, 2021)
Total knee arthroplasty (TKA) is a surgery method that can reduce symptoms and restore joint functions. Long-term success of this operation depends on the correct anatomical and mechanical planning before the prosthetic material implantation. Accurate implant alignment together with anatomical balance provides more successful clinical outcomes and longer duration of the prosthetic material. Improper preoperative planning may cause implant loosening and increased load on the knee joint. Conventional radiographs are the most frequently used imaging methods for this purpose. Computed tomography and magnetic resonance imaging may be used in required cases. In addition, computer-aided systems have come into use and successful results have been reported. Early radiographic evaluation is unnecessary after an uncomplicated TKA. Preoperative imaging has several aims such as to assess the severity of the disease, to analyze the reserve bone tissue, to review the relevant anatomy, and to decide which implant and surgical approach will be applied. In this article, we aimed to present the necessary and also auxiliary radiological evaluations made before TKA in order to achieve better clinical results.